The field of knowledge of the environmental management paradigm. (9th May 2019) - Díaz-Rodríguez, Carlos; Yate-Arévalo, Abdénago; Sánchez-Buendía, Edgar Emilio
The environmental management paradigm facilitates organisations' adaptation and flexibility using ethical and bioethical criteria for the management of physical, chemical, and biological processes and their interactions with humanity not to mention their environmental impact. Traditional management is insufficient to meet the demands of uncertainty and unpredictability, as well as the complexity of environmental impacts. The environmental paradigm integrates the social and the natural but it does not offer methods and tools to develop a practical solution for environmental problems to move towards sustainable development.